The Effectiveness of the Discovery Learning Model Assisted by Cermat Multimedia on Cartesian Coordinate Material - Bito, Nursiya; Riswan, Riswan; Pauweni, Khardiyawan A.Y. (Department of Mathematics, Universitas Negeri Gorontalo, 2024)
This descriptive research aims to evaluate the effectiveness of the Discovery Learning model assisted by Cermat multimedia in teaching the topic of Cartesian coordinates at SMP Negeri 11 Gorontalo. The study examines three key aspects: (1) the teacher's proficiency in managing the learning process, (2) students' positive responses to the learning approach, and (3) students' learning outcomes. The findings indicate that the Discovery Learning model supported by Cermat multimedia is highly effective. This conclusion is supported by the teacher's performance in managing the learning process, categorized as excellent, students' consistently positive responses throughout the learning activities, and the attainment of an 80% mastery level in learning outcomes on a class-wide basis.